The Influence of Self Leadership on Task Commitment Through Self-Efficacy Mediation in Students - Agustina Agustina; Rahmi Lubis; Siti Aisyah (Bulletin of Counseling and Psychotherapy)
This study uses quantitative research methods. The population and samples used were students. The research instrument was a questionnaire, namely aspects of task commitment, self-leadership and self-efficacy. The data analysis method used is SEM-PLS. The results showed hypothesis 1 there is an influence of self-leadership (X) on self-efficacy (M). This influence can be seen from the strength of the relationship (R-value) of 0.542 which is classified as sufficient with an R Square value of 0.293 or 29.3%. This means that the self-leadership variable has a direct effect of 29.3% on self-efficacy. Hypothesis 2 of this study is the effect of self-efficacy on task commitment. This hypothesis is proven correct because the significance value is 0.000 <0.05. The effect can also be seen in the Summary table with an influence strength value (R-value) of 0.549 and a coefficient of determination of 0.302 or 30.2%. This means that the self-efficacy variable (M) has a direct effect of 30.2% on task commitment. Hypothesis 3, namely that there is an effect of self-leadership on task commitment through self-efficacy, this hypothesis is proven by the significance value in the regression coefficient table of 0.000 <0.05. while the calculated R value is 0.580. the coefficient of determination obtained a value of 0.336 or 33.6%. This means that the variables of self-leadership and self-efficacy have an indirect effect of 33.6% on task commitment.